2007
DOI: 10.1177/0010414006292113
|View full text |Cite
|
Sign up to set email alerts
|

Leadership, Party, and Religion: Explaining Voting Behavior in Indonesia

Abstract: This case study tests the significance of leadership, party identification, religious orientation, political economy, and sociological and demographic factors in the legislative and presidential choices of voters in the new Indonesian democracy. Data were obtained from four national opinion surveys conducted by the authors following parliamentary elections in 1999 and 2004 and the two-round presidential election in 2004. Bivariate and multivariate analyses of our data confirm the significance of leadership and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
75
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(82 citation statements)
references
References 18 publications
1
75
0
6
Order By: Relevance
“…The dominant factors include: media, social status and class, party leadership, age, education, religion, ethnicity, gender, voter origin region and the last is pooling results (Ali & Lin, 2013;Liddle & Mujani, 2007). This dominant factor is expected to make every election very interesting in Indonesia.…”
Section: Indonesian Voters' Behaviormentioning
confidence: 99%
See 2 more Smart Citations
“…The dominant factors include: media, social status and class, party leadership, age, education, religion, ethnicity, gender, voter origin region and the last is pooling results (Ali & Lin, 2013;Liddle & Mujani, 2007). This dominant factor is expected to make every election very interesting in Indonesia.…”
Section: Indonesian Voters' Behaviormentioning
confidence: 99%
“…It has a wide and effective influence to change voter preference and views (Liddle & Mujani, 2007). There are three main strategies of the media in influencing voter preferences in Indonesia; (1) bringing news and opinions to certain issues, such as religion and welfare, (2) the media also have the ability to focus on certain news and topics, (3) media can directly influence voters by continuously creating biased news.…”
Section: Indonesian Voters' Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…All three voting behavior models above are basically categorized by decisive factors of voting determinants of a person or group of persons (see Niemi 2008: 13-15;Evans, 2004;6-89;Heywood, 2007: 265-269;Liddle and Mujani, 2007). However, in addition to categorization of the models, voting behavior can also go through concepts of: (1) compliance of voters (Schaffer, 2005: 3-4;Schaffer, 2007: 17-29); (2) loyalty of voters (Hirschman, 1970;Anderson and Srinivasan, 2003;Evans, 2004;Bratton, 2008: 15;Bartels, 2008;14;Scaffer, 2007: 185); (3) the decision to select or choose a specific selection (see Redlawsk, 2006: 3-8;Evans, 2004: 4;Vicente 2007: 18;Woshinsky, 2008: 102-132;Zulkerman, 2005;229) Based on the previous reference, the author feels it is important to conduct a special study on the relationship between voting behavior and vote buying.…”
Section: Robi Cahyadi Kurniawan Et Al Vote Buying In Lampung Localmentioning
confidence: 99%
“…It has even been suggested that religion contributes to a growing polarisation of public opinion in the United States, although empirical evidence on this claim is rather mixed (Lehrer, 2004;Fiorina 2005). In other political systems too, religion has been shown to have a strong impact on voting behaviour (Liddle and Mujani, 2007).…”
Section: Introductionmentioning
confidence: 99%